Karbon Aktif Berkelanjutan dari Limbah Bonggol Pisang: Karakterisasi dan Kinerja Adsorpsi untuk Limbah Industri - Irsyadul Ibad, Mochamad; Bashori, Hasan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study investigates the use of banana corm waste as a raw material for producing activated carbon for textile wastewater treatment. The objective of the research was to produce activated carbon from banana corms using potassium hydroxide (KOH) and sulfuric acid (H₂SO₄) as activating agents, and to evaluate its adsorption performance on methylene blue dye. The activated carbon was prepared through carbonization at 250°C, followed by chemical activation using KOH and H₂SO₄, washing to neutral pH, and drying. The characterization included moisture content, ash content, iodine adsorption capacity, methylene blue adsorption, and UV-Vis spectrophotometric analysis. The results showed that H₂SO₄-activated carbon exhibited higher methylene blue adsorption capacity compared to KOH-activated carbon, while KOH-activated carbon had lower ash content. Overall, the activated carbon derived from banana corms met the quality standards for activated carbon in terms of moisture, ash, and iodine adsorption. These findings indicate that banana corm-based activated carbon has potential as an eco-friendly, effective adsorbent for removing dye pollutants from textile wastewater.